2018
DOI: 10.1186/s12958-018-0328-z
|View full text |Cite
|
Sign up to set email alerts
|

Maternal physical activity before IVF/ICSI cycles improves clinical pregnancy rate and live birth rate: a systematic review and meta-analysis

Abstract: ObjectiveThis meta-analysis was aimed to evaluate the association between maternal physical activity before IVF/ICSI cycles and reproductive outcomes.MethodsWe searched databases of PubMed, EMBASE and Web of Science electronic databases, and ongoing trials up to November 2017 to identify studies that focused on the relationship between maternal physical activity before IVF/ICSI cycles and reproductive outcomes, including implantation rate, clinical pregnancy rate, miscarriage rate and live birth rate. Odds rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(28 citation statements)
references
References 41 publications
2
25
0
1
Order By: Relevance
“…Recently, findings from the Environment and Reproductive Health (EARTH) Study 45 suggested that time spent in moderate-to-vigorous physical activities before IVF was not associated with probability of implantation, clinical pregnancy or live birth, in 273 women who underwent 427 IVF cycles. Pooled estimates from a recent meta-analysis 16 suggested a beneficial effect of PA on ART outcomes, and no effect on spontaneous abortion; despite this, study results are widely heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, findings from the Environment and Reproductive Health (EARTH) Study 45 suggested that time spent in moderate-to-vigorous physical activities before IVF was not associated with probability of implantation, clinical pregnancy or live birth, in 273 women who underwent 427 IVF cycles. Pooled estimates from a recent meta-analysis 16 suggested a beneficial effect of PA on ART outcomes, and no effect on spontaneous abortion; despite this, study results are widely heterogeneous.…”
Section: Discussionmentioning
confidence: 99%
“…15 This evidence has been recently reviewed: pooled estimates from a systematic research found that PA before ART cycles was associated with increased rates of clinical pregnancy and live births, but no effect was shown on miscarriage rate. 16 These factors have been analysed in relation to sperm quality. Several reviews showed that the same lifestyle habits, such as smoking and regular drinking, negatively impacting female fertility, also have a detrimental effect on semen quality.…”
Section: Open Accessmentioning
confidence: 99%
See 1 more Smart Citation
“…However, couples attempting conception or couples seeking infertility treatment do not currently know whether higher/lower levels of PA can increase or reduce the chances of becoming pregnant and having live birth. In fact, no consensus has been reached regarding the effect of PA during ART on pregnancy outcomes [ 15 ]. The few studies of female and male PA in association with ART success have reported mixed results [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, no consensus has been reached regarding the effect of PA during ART on pregnancy outcomes [ 15 ]. The few studies of female and male PA in association with ART success have reported mixed results [ 15 , 16 , 17 , 18 , 19 , 20 , 21 ]. Nevertheless, the general belief is that doing regular PA is good for female [ 6 , 7 , 22 ] and male fertility [ 17 , 18 , 19 , 23 , 24 ], while high intensity and frequency of PA [ 25 ] or low PA or extensive sedentary time can increase subfertility and infertility [ 19 , 23 , 26 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%